THE CURRENT ISSUES ON THE IMPACT OF MONOSODIUM GLUTAMATE FOOD ADDITIVE ON THE VISUAL ORGAN AND THE HUMAN BODY - Synenko, V.A.; Yeroshenko, G.A.; Shevchenko, K.V.; Klepets, O.V.; Grygorenko, A.S.; Соколенко, В.М.; Sharlay, N.M. (World of Medicine and Biology, 2024)
To investigate the impact of monosodium glutamate on the visual organ, specifically on the posterior segment of the eye, and the body as a whole, as how regular consumption of such an additive can affect health over time. The analysis of scientific data on the impact of monosodium glutamate on the retina of the eye, aimed at better understanding the potential risks and mechanisms of action of this substance. Particular attention is given to studying the mechanisms of monosodium glutamate’s neurotoxicity, its effects on photoreceptors and retinal ganglion cells, as well as the potential long-term consequences of excessive consumption of this food additive. Analytical research methods were used in the writing of the article. The literature data on the use of monosodium glutamate in food products and its effects on the retina of the eye and the body as a whole have been analyzed and summarized. Determining the degree of negative impact of the food additive on the retina will enable timely prevention and detection of retinal damage, which, in turn, will help prevent vision loss in the patient.